Porosity‐Controlled Eggshell Membrane as 3D SERS‐Active Substrate1. Issue 8 (3rd March 2014) - Lin, Pei‐Ying; Hsieh, Chiung‐Wen; Tsai, Pei‐Chuan; Hsieh, Shuchen
Abstract We report on the fabrication of a surface‐enhanced Raman scattering (SERS) platform, comprised of a three‐dimensional (3D) porous eggshell membrane (ESM) scaffold decorated with Ag nanoparticles (NPs). Both native and treated ESM were used, where the treated ESM pore size and fiber crossing density was controlled by timed exposure to hydrogen peroxide (H2O2). Ag NPs were synthesized in situ by reduction of silver nitrate with ascorbic acid. Our results demonstrate that H2O2‐treated Ag‐ESM provides a more densely packed 3D network of active material, which leads to consistently higher SERS enhancement than untreated Ag‐ESM substrates.